A clinical study of pemphigus vulgaris and its variants, evaluation of safety and efficacy of glucocorticoids versus immunosuppressants at tertiary care hospital: a study of 75 cases - Chotaliya, Kiran; Kantaria, Darshil Shailesh; Patel, Raksha; Desai, Krishna (International Journal of Research in Dermatology, 2025)
Background: Pemphigus is an autoimmune blistering disorder affecting skin and mucous membranes. Autoantibodies target desmoglein proteins, leading to acantholysis. Glucocorticoids (GCs) are the primary treatment, but long-term use leads to side effects, prompting the use of other immunosuppressants like cyclophosphamide, rituximab, azathioprine, methotraxate for steroid-sparing effects. Methods: Seventy-five pemphigus patients were included. Diagnoses were based on clinical and histopathological findings. Patients were treated with GCs alone or in combination with immunosuppressants like cyclophosphamide, rituximab, azathioprine, methotraxate. Clinical remission and adverse events recorded over an 18-month follow-up. Results: The 46 patients were treated with GCs alone, while 19 received additional cyclophosphamide. 89.5% of patients treated with GCs and cyclophosphamide achieved remission within 4 months, compared to 73.9% with GCs alone. Conclusions: Cyclophosphamide and other immunosuppressants enhances clinical outcomes by achieving earlier remission and reducing relapse rates in pemphigus patients compared to GCs alone. Its use as an adjunct may offer significant steroid-sparing effects.